KEPEMIMPINAN KETUA YAYASAN BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI LEMBAGA PENDIDIKAN PONDOK PESANTREN ASH-SHOBIRIN - Muhammad Kafiyanto; Suharto; Muhammad Yasin (UNISAN JURNAL, 2024)
The success of education at an educational institution that oversees the Foundation is determined by various factors, one of which is the Chair of the Foundation. There are several points of view in looking at someone’s personality based on their intelligence. Emotional intelligence is one point of view that is able to analyze the leadership of a foundation chairman. The Ash-Shobirin Islamic Boarding School Educational Institution Foundation is one of the foundations currently developing in Indonesia. The leadership of the chairman of the Foundation based on emotional intelligence (EQ) is considered very good. This has a positive impact on the sustainability of the organization’s foundation. Therefore, researchers tried to analyze the leadership of the head of the Ash-Shobirin Islamic Boarding School educational institution focusing on the perspective of his emotional intelligence. This research is a qualitative study that describes the leadership of the Chair of the Ash-Shobirin Islamic Boarding School Educational Institution and analyzes the perspective of emotional intelligence. This research was conducted using observation, interview and documentation techniques. Testing the validity of the data uses triangulation techniques, which in this research emphasizes the source of the triangulation technique. The resource persons were all the foundation’s residents, including the council, the environment, the people around them, including elementary, middle and vocational school teachers at the Ash-Shobirin Islamic Boarding School. This source will contain data on the leadership of the Ash-Shobirin Islamic Boarding School Foundation based on emotional intelligence. The research results show that the Chair of the Ash-Shobirin Islamic Boarding School Foundation has good leadership in terms of emotional intelligence. The results of the analysis show that the chairman of the foundation carries out primal leadership very well. This is proven by triangulation of data and sources. The chairman of the Ash-Shobirin Islamic Boarding School Intercession Institution has a high commitment to the vision of the future, especially in times of stress or in the midst of increasing responsibilities. The chairman of the foundation took an emotional approach to all foundation members. The Foundation Chair can read his own emotions and recognize their impact using actions to direct decisions, knows his strengths and limitations, can control his emotions and demonstrate honesty and integrity, can be trusted. The Chairman of the Foundation has good self-awareness and self-management, good social awareness and good relationship management.